Pengaruh Penerapan Model Pembelajaran Discovery Learning berbantuan Multimedia Wayground terhadap Literasi Budaya Tolitoli Siswa Kelas V SDN 2 Nalu - Syaiful Hidayat; Moh Rudini; Mustakim (Tolis Ilmiah : Jurnal Penelitian, 2026)
Low cultural literacy among the younger generation, particularly in relation to the local wisdom of Tolitoli, which is beginning to deteriorate, calls for innovative contextual and interactive learning models. This study examines the effect of applying a discovery learning model supported by Wayground multimedia on the cultural literacy level of fifth-grade students at SD Negeri 2 Nalu. The methodological approach adopted was quasi-experimental, applying a non-equivalent control group design, in which the research participants included 34 students distributed into two categories, namely the experimental group and the control group. The data collection mechanism was carried out through test instruments (including pre-tests and post-tests) supplemented by observations of learning activities. Data analysis revealed a substantial escalation of cultural literacy in the experimental group, which recorded a post-test average of 88.88 and an N-Gain score of 0.66 (moderate criteria); this achievement exceeded that of the control group, which only obtained an average of 70.12 with an N-Gain of 0.019 (low criteria). Furthermore, hypothesis testing using the Mann-Whitney U test showed a significance value of 0.001 (p < 0.05), indicating rejection of the null hypothesis. Thus, it can be concluded that the integration of the Wayground multimedia-based discovery learning model has a significant effect in boosting students' Tolitoli cultural literacy, while also proving effective in creating a participatory learning climate and offering innovative solutions for cultural value preservation efforts at the elementary school level.